A Lycium barbarum extract inhibits β‐amyloid toxicity by activating the antioxidant system and mtUPR in a Caenorhabditis elegans model of Alzheimer's disease. Issue 2 (19th January 2022) - Meng, Jiao; Lv, Zhenyu; Guo, Miaomiao; Sun, Chuanxin; Li, Xiaopeng; Jiang, Zhenguo; Zhang, Wanchang; Chen, Chang
Abstract: Lycium barbarum, a traditional Chinese medicine, has been shown to have antioxidant properties and has a protective effect in many diseases related to oxidative stress, such as neurodegenerative diseases, cardiovascular diseases, and cancer. Although the neuroprotective effects of L. barbarum extract (LBE) have been reported in several studies, the underlying molecular mechanisms are still unclear. In this study, the transgenic Caenorhabditis elegans strain CL2006 was used to investigate the function and molecular mechanism of an LBE in Alzheimer's disease (AD). LBE had high antioxidant potential and effectively delayed Aβ‐induced paralysis in the CL2006 strain. LBE inhibited the production of excessive reactive oxygen species by inducing the SKN‐1‐mediated antioxidant system, thereby inhibiting the generation of Aβ and inhibiting mitochondrial damage. Importantly, LBE reduced Aβ levels by inducing FSHR‐1‐mediated activation of the mtUPR. Therefore, our study not only reveals a new mechanism of LBE in the treatment of AD but also identifies a novel strategy for the treatment of AD by enhancing the mtUPR.